The antiviral effects of acteoside and the underlying IFN-γ-inducing action. Issue 7 (21st June 2016) - Song, Xun; He, Jiang; Xu, Hong; Hu, Xiao-Peng; Wu, Xu-Li; Wu, Hai-Qiang; Liu, Li-Zhong; Liao, Cheng-Hui; Zeng, Yong; Li, Yan; Hao, Yue; Xu, Chen-Shu; et al.
Abstract : Acteoside, a natural phenylpropanoid glycoside from Kuding Tea, enhanced IFN-γ production in mouse lymphocytes in a dose-dependent manner, particularly in the CD4+ and CD8+ subsets of T lymphocytes. Abstract : There are many herbal teas that are found in nature that may be effective at treating the symptoms and also shortening the duration of viral infections. When combating viral infections, T lymphocytes are an indispensable part of human acquired immunity. However, studies on the use of natural products in stimulating lymphocyte-mediated interferon-gamma (IFN-γ) production are very limited. In this study, we found that acteoside, a natural phenylpropanoid glycoside from Kuding Tea, enhanced IFN-γ production in mouse lymphocytes in a dose-dependent manner, particularly in the CD4+ and CD8+ subsets of T lymphocytes. To this end, we suggest that the antiviral activity of acteoside was highly correlated to its inducing ability of IFN-γ production. Mechanistically, the activation of T-bet enhanced the promoter of IFN-γ and subsequently resulted in an increased IFN-γ production in T cells. Collectively, we have found a natural product with the capacity to selectively enhance mouse T cell IFN-γ production. Given the role of IFN-γ in the immune system, further studies to clarify the role of acteoside in inducing IFN-γ and prevention of viral infection are needed.